The house that made me: writers reflect on the places and people that defined them - Jarrett, Grant (SparkPress, a BookSparks imprint, a division of SparkPoint Studio, LLC, 2016)
A group of authors reflect on the places and people that defined their lives. They are: Lee Upton, Tim Johnston, Antonya Nelson, Ru Freeman, Grant Jarrett, Meg Tuite, Patricia Jabbeh Wesley, Paul McVeigh, Julie, Metz, Ellen Meister, Pamela Erens, Jeffery Renard Allen, Alice Eve Cohen, Porochista Khakpour, Laura Miller,Justine Musk, Jen Michalski, Jen Michalski, Kris Radish and Roy Kesey.